Faktor Yang Berhubungan Dengan Tumbuh Kembang Anak 0-59 Bulan Di Puskesmas Pintu Angin Kota Sibolga Tahun 2023 - AGUSTINA PASARIBU; Magdalena Br Barus (Calory Journal Medical Laboratory Journal, 2023)
Children are the next generation of the nation, so children with good qualities are needed in order to achieve a quality future for the nation. This research aims to determine factors related to the growth and development of children aged 0-59 months at the Puskesmas Pintu Angin, Sibolga in 2023. This type of research is a survey type with a cross sectional design. The population in this study are 50 people. The sample in this study used a total sampling of 50 people. The test carried out was Chi-square. There is a relationship between birth weight and the growth and development of children aged 0-59 months with a p-value of 0.04, there is a relationship between parental income and the growth and development of children aged 0-59 months with a p-value of 0.02, there is a relationship between the number of siblings under five and Growth and Development of Children 0-59 Months with a p-value of 0.04. There is a relationship between parental education and the Growth and Development of Children 0-59 Months with a p-value of 0.02. It is hoped that Posyandu cadres can hold an outreach program for mothers with toddlers regarding the importance of efforts to improve nutrition for families, especially toddlers.